The Numerical Simulation of Propeller Sheet Cavitation with a New Cavitation Model. (2015) - Liu, Dengcheng
Abstract: According to the mass transport equations of vapor and liquid, and Rayleigh-Plesset equation, a cavitation model based on a single-fluid multi-phase flow method is proposed, which especially considers the nonlinear variety of the bubble radius and is expected to deal well with cloud cavitating flow.The proposed cavitaion model was validated against a benchmark database for 2D NACA66MOD hydrofoil and experimental photos of E779A propeller sheet cavitation shape. The overall results suggest that the present proposed cavitation model is practicable for simulating cavitating flows.